Verwandtschaft, Name und soziale Ordnung (300 - 1000) - Patzold, Steffen 1972-; Beck, Heinrich 1929-2019; Kongress (Reallexikon der germanischen Altertumskunde Ergänzungsbände zum Reallexikon der germanischen Altertumskunde ; Bd. 90, 2014)
"The social transformation of the Roman world is a highly topical and much-discussed subject among historians. The importance of kinship in this epochal process has been largely neglected until now. This compendium seeks to close this gap by examining the role of kinship in transforming the social order. It significantly expands our perspective on the epochal upheaval between late antiquity and the middle ages"--